Queijo Minas artesanal da Serra da Canastra: influência da altitude e do nível de cadastramento das queijarias nas características físico- químicas e microbiológicas - Maria de Fatima Silva de Resende (2010)
The production of Minas artisanal cheese is traditional in Minas Gerais State and there are few data about the microbiota present in this food. The influences of altitude and official registration at the state inspection office (SIO) on the microbiological and physical-chemical characteristics of Serra da Canastra Minas artisanal cheese were evaluated. Samples of milk, cheese whey, and cheese from 18 rural properties were analyzed. Means of most probable number of coliforms in cheeses were different (P<0.05) considering the registration at the SIO. Staphylococcus spp. was found in high numbers in cheeses, irrespectively of the studied factors. Salmonella spp. was not isolated in the samples of cheese. High counts of lactic acid bacteria (LAB) were observed in all samples, being mostly affected by the altitude. Enterococcus, Lactococcus, and Lactobacillus were predominantly identified (PCR ARDRA-16S-23S) in milk, cheese whey, and cheese samples, respectively. In cheeses, Lactobacillus rhamnosus, Lactobacillus casei, and Lactobacillus plantarum were the major LAB. Lactobacillus hilgardii and Lactobacillus paraplantarum were also identified and it is probably the first description of these LAB in artisanal cheese. Indeed, improvement in this cheese making is strongly recommended in order to obtain a uniform quality product considering it as a Brazilian Cultural Patrimony